Calibration of MTT assay in proton beams using radiochromic films. (September 2020) - Moftah, B.; Aldelaijan, S.; Shehadeh, M.; Alzorkany, F.; Alrumayan, F.; Alsbeih, G.; Alshabanah, M.; Seuntjens, J.; Tomic, N.; Devic, S.
Highlights: Low energy proton beams. Radiochromic film dosimetry. Dose calibration for radiobiological experiments. Abstract: Purpose: This study provides methodology of calibrating as well as controlling the output for an MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) colorimetric assay irradiated in a low energy proton beam using EBT3-model GAFCHROMIC TM film, without correcting for quenching effect. Methods: A calibrated Markus ionization chamber was used to measure the depth dose and beam output for 26.5 MeV protons produced by a CS30 cyclotron. A time-controlled aluminum cylinder was added in front of the horizontal beam-exit serving as a radiation shutter. Following the TRS-398 reference dosimetry protocol for proton beams, the output was calibrated in water at a reference depth of 3 mm. EBT3 film was calibrated for doses up to 8 Gy at the same depth. To verify the dose distribution for each 96-well MTT assay plate, EBT3 film was placed at the reference depth during irradiation and cell doses were scaled by measured percent depth dose (PDD) data. Results: The radiochromic film dosimetry system in this study provides dose measurements with an uncertainty better than 3.3% for doses higher than 1 Gy. From a single exposure and utilizing the Gaussian shape of the beam, multiple dose points can be obtained within different wells of the same plate ranging from 6.9 Gy (sigma ∼4%) in the central well, and 2 Gy (sigma ∼8%) for wells positioned closer to the periphery. Conclusions: We described a methodology for radiochromic film-based dose monitoring system, using low-energy protons, which can be used for the MTT assay in any proton beam, except within Bragg peak region.